Public participation, democratic decision-making, and extractive resource management in Greenland - Doering, NN (2019)
Extractive resource development has been viewed as a way for Greenland to increase its financial and political independence from Denmark. However, while Greenland’s government has actively promoted the country’s resources abroad, criticism over lack of proper public involvement in decision-making has grown in recent years. This thesis examines the dynamics that shape participation and non-participation in Greenland. The core of the thesis consists of four empirical chapters, which approach the topic from different perspectives. First, a major reform of Greenland’s municipal structure is analysed. This provides important insights into the relationship between citizens and decision-makers. Second, barriers to participation in public consultation meetings, which form a required part of the licensing process, are explored to understand low attendance levels. Third, efforts of NGOs and environmental groups for improved participation are considered. Finally, a focus is placed on young people’s participation. The thesis is based on semi-structured interviews, a survey, and participant observation. Fieldwork took place between September 2015 and the beginning of June 2016 in Aasiaat, Ilulissat, Sisimiut, and Nuuk. Aasiaat had previously served as a supply base for oil exploration activities in the region and was chosen as the main field site.